HEALTHY LIFESTYLE INSTRUMENT - Mohd Fazil, Azlan Faizal; Mohammad Noor, Nurfaizura Fazana; Mustafa Khalid, Nur Izyan; Lop Ahmad, Hanun Nasuha; Ismail, Suzilah; Kamarudin, Norehan (Journal of Human Capital Development (JHCD), 2019)
The main purpose of this study was to develop an instrument to measure the Healthy Lifestyle among employees of KPTM Ipoh, KPTM Alor Setar, UniSHAMS and Intel Kulim. The sample was collected using self-administered questionnaire from 16 people for our focus group based on our sampling frame design and distributed four instruments for each strata group. The total instrument from the pilot study are 64 instruments. Three (3) constructs of the Healthy Lifestyle Instrument primarily consist of Fitness Wellness, Dietary Wellness and Behavior Wellness. The result of descriptive analysis show that the alpha reliability of the construct items in healthy lifestyle are acceptable. This would be express that the Healthy Lifestyle Instrument be considered reliable. However, in the exploratory factor analysis show that the findings are expanded from three factors to seven factors of employee healthy lifestyle practices. As related to this and previous analysis, we conclude that the Healthy Lifestyle Instrument are valid and reliable. However, this will require full data collection in order to fully validate the instrument. Therefore, the 3 aspects of employee’s healthy lifestyle practices will remain the same as before the test performed. This is due to small sample size in pilot study. The same analysis procedure will be performed using sufficient sample size. However, in term of factor analysis in the main study, the finding of new emerge factors from the previous pilot study will be executed in order to conclude the final factoring involve. Keywords: health, lifestyles, exploratory factor analysis